TAXONOMY, DISTRIBUTION AND DIVERSITY OF PLANKTONIC ALGAE AT PINDIGA DAM, NIGERIA - A. ZHIGILA, DANIEL; B. HUSSAINI, UMMULKHURSUM; ADAMU GARKUWA, NURU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2022)
Taxonomic identification of algae at both generic and species levels is problematic owing to several reasons including cells’ fragility, sensitivity to chemical fixatives and inconspicuous morphological features. The planktonic algae in tropical African dams have been particularlyproblematic given the paucity of algal taxonomic experts in this region. In this study, we present for the first time the taxonomic and geographic appraisal of planktonic Algae at Pindiga Dam. Further, planktonic algal flora and its monthly variations at the Pindiga Dam were investigated. The study revealed a total of 35 genera. Species in the family Chlorophyceae were the most abundant (42%), followed by those in the families Bacillariophyceae (38%) and Charophyceae (25%). Other taxonomic groups present were Chryophyceae, Cryptophyceae, Cynophyceae and Euglenophyta (7%) each. Trachelomonas, Tetrahedrom and Pleurozester were the most abundant taxa. The Important Value Index (IVI) and species diversity of algae are dependent on the sampling month. For instance, Trachelomonas recorded the highest IVI (23.67) and the lowest was recorded by Cryptomonas (8.18) in April, but it was observed that in May; Tetrahedrom recorded the highest IVI (22.57) and the lowest was recorded by Zygnema (9.38). In June, another set of taxa recorded the highest and the Lowest IVI namely: Pleurogaster, Crucigenia (17.63) and Netrium, Oedogenium (8.93) each. The composition of planktonic algae families in Pindiga Dam could be said to be Chlorophyceae, Bacillariophyceae, and Cyanophyceae in order of the IVI. The Simpson’s index of diversity of planktonic algae at Pindiga Dam was 0.94542, 0.94708 and 0.95364 in April, May and June respectively. The species richness in April was 1.97, in May was 1.92 and in June was 2.10. The values were high indicating a more complex plankton community with a good measure of abundance and diversity. This study has provided baseline information on the taxonomy, distribution and diversity of planktonic algae in Pindiga Dam. This knowledge is useful to groups involved in water utilities; irrigation and drainage districts, industries, private pond owners, fish farmers and aqua culturist.